Gender Differences in Language as Affected by Social Roles - Hysi, Eglantina (Mediterranean Journal of Social Sciences, 2012)
Variations in language, besides other factors, seem to be direct and significant products of gender variable. Thedivision of society into men and women, both being different and complex, is reflected in various forms in language which is themost important means of communication among them. The article will focus on variations related to gender of speakers. It willreveal differences that are found in the language of women and men, and will link these differences with the social roles that areassigned to them in Albanian society (and other countries) as well as with the socio-cultural environment where they live. Hencewe will present gender-related pecularities that give insight into the position of women and their status. It appears that rules laidupon them have made their language more hesitant, indirect and euphemistic. However, their speech inevitably reveals theirexpressive and emotional nature especially while relating to their children.